PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF ONLINE POKOK BAHASAN BARISAN ARITMETIKA BERBANTUAN MICROSOFT VISUAL BASIC - Faruq, Fathulloh; Dafik, D; Suharto, S; Fatahillah, Arif; Murtikusuma, Randi Pratama (Kadikma, 2018)
Abstract. The purpose of this research was to produce a product to attract students’ interest in learning mathematics tested the validity, practicality, and effectiveness of using development interactive learning media of arithmetic squence. The role of technology in the field of education is not only limited to how to operate a computer, but is expected to be a solution to learning problems experienced by students and teachers. This research was processed through the stages of 4D that is define, design, development, and disseminate. This research was conducted in MAN 1 Jember which involved 32 students’ of class XII MIPA 2. The result of the research show that the development media is valid according to the material expert with the percentage of the archieved value 93,75% from validator I, 95,31% from validator II, and validator III gives 92,19% value. Effective media with learning test reasult followed 32 students’ in this research show 87,5% completed. Quationnaire showed a percentage of a 85,27% from student for practicality. Keywords: Development, Media, Technology